High Levels of the Xenorhabdus nematophila Transcription Factor Lrp Promote Mutualism with the Steinernema carpocapsae Nematode Host - Cao, Mengyi (Appl Environ Microbiol, 2017)
Xenorhabdus nematophila bacteria are mutualistic symbionts of Steinernema carpocapsae nematodes and pathogens of insects. The X. nematophila global regulator Lrp controls the expression of many genes involved in both mutualism and pathogenic activities, suggesting a role in the transition between the two host organisms. We previously reported that natural populations of X. nematophila exhibit various levels of Lrp expression and that cells expressing relatively low levels of Lrp are optimized for virulence in the insect Manduca sexta. The adaptive advantage of the high-Lrp-expressing state was not established. Here we used strains engineered to express constitutively high or low levels of Lrp to test the model in which high-Lrp-expressing cells are adapted for mutualistic activities with the nematode host. We demonstrate that high-Lrp cells form more robust biofilms in laboratory media than do low-Lrp cells, which may reflect adherence to host tissues. Also, our data showed that nematodes cultivated with high-Lrp strains are more frequently colonized than are those associated with low-Lrp strains. Taken together, these data support the idea that high-Lrp cells have an advantage in tissue adherence and colonization initiation. Furthermore, our data show that high-Lrp-expressing strains better support nematode reproduction than do their low-Lrp counterparts under both in vitro and in vivo conditions. Our data indicate that heterogeneity of Lrp expression in X. nematophila populations provides diverse cell populations adapted to both pathogenic (low-Lrp) and mutualistic (high-Lrp) states. IMPORTANCE Host-associated bacteria experience fluctuating conditions during both residence within an individual host and transmission between hosts. For bacteria that engage in evolutionarily stable, long-term relationships with particular hosts, these fluctuations provide selective pressure for the emergence of adaptive regulatory mechanisms. Here we present evidence that the bacterium Xenorhabdus nematophila uses various levels of the transcription factor Lrp to optimize its association with its two animal hosts, nematodes and insects, with which it behaves as a mutualist and a pathogen, respectively. Building on our previous finding that relatively low cellular levels of Lrp are optimal for pathogenesis, we demonstrate that, conversely, high levels of Lrp promote mutualistic activities with the Steinernema carpocapsae nematode host. These data suggest that X. nematophila has evolved to utilize phenotypic variation between high- and low-Lrp-expression states to optimize its alternating behaviors as a mutualist and a pathogen.